GAMBARAN FAKTOR PEMBERIAN ASI EKSLUSIF PADA BAYI DI DESA KEMUNING LOR KECAMATAN ARJASA KABUPATEN JEMBER - Zayniyyatul Ma’rufah; Musia; Zaida Maulidyah (LPPM Universitas dr. Soebandi, 2016)
Breastfeeding is the best food for a baby at the early of life. When breastfeeding is very important, but not all mothers do. Exclusive coverage of breastfeeding in Jember is 66.37% while attainment targets is 80% one of them in Arjasa. Based on the survey result obtained 60% mother is not exsclusively breastfeed their baby. Purpose of this research is identify factors of exclusive breastfeeding in Kemuning Lor Village Arjasa Sub District Jember City. This type of researchis descriptive. Population in this research are all the mothers have baby aged 7-12 months is 31 people with the sampling technique is random sampling. Analyzed file using a computer with statistical product and service solution (SPSS) 16.0 for windows. Exclusive of breastfeeding in Kemuning Lor Village, Arjasa Sub-District, Jember City. Tends do by mothers with the last school is high school (51,6%) housewife 13 (41,9%) and mother with a good level of knowledge 16 (51,6%). The conclusion in this research that breasfeeding in Kemuning Lor Village, Arjasa Sub-District, Jember City tends do by mother with secondary education, the mother doesn’t work, and has a good knowledge